Sex-related differences in dietary phytochemical intake in the population of primary school children in urban setting - Bituh, Martina; Ilić, Ana; Škorvaga, Petra; Brečić, Ružica; Colić Barić, Irena; Rumbak, Ivana (Frontiers in Nutrition, 2025)
BackgroundThe consumption of phytochemicals is known for its positive effects on human health. However, there are no established recommendations for daily intake in European or international guidelines. Given the different dietary patterns in different countries and the changes in dietary trends over time, it is crucial to assess the intake of phytochemicals, especially in children, as inadequate consumption may increase the risk of chronic non-communicable diseases. To address this gap, the present study aims to estimate the daily intake of the four major classes of phytochemicals among schoolchildren in urban areas and to identify the main dietary sources and subclasses that contribute most to their intake.MethodsDaily intake of the four main classes of phytochemicals and their main dietary sources was assessed in school children from an urban setting (N = 195; 8.9 ± 0.4 years). Intake of phytochemicals was estimated from 3-day dietary records analyzed with available composition tables and databases.ResultsThe median intake of polyphenols in children was 125.7 mg/day, of carotenoids 3.9 mg/day, of phytosterols 126.1 mg/day and of glucosinolates 2.3 mg/day, with girls having a significantly higher intake of polyphenols. Although fruit and vegetables are the most common sources of phytochemicals in the diet, an increased contribution of sweets and cakes and mixed dishes was observed. Food groups rich in phytochemicals (fruits, vegetables, legumes, nuts and seeds) contributed less than 10% of the daily energy intake.ConclusionAlthough there are no official recommendations for the intake of phytochemicals, the study suggests that children have a low intake of all four main classes of phytochemicals compared to existing data for both children and adults. To improve the intake of phytochemicals, it is necessary to promote the consumption of foods rich in phytochemicals and increase dietary diversity both at home and at school.